Influence of Low Intensity Pulsed Ultrasound on Enhancing Biostimulation of Median Nerve in Patients with Chronic Carpal Tunnel Syndrome - Amin, Fatma Sedik; Hassan, Fahd Abdelazim; Saleh, Rehab Abdelhafiez; Fahmy, Ebtesam Mohamed; Lasheen, Yasser Ramzy (Journal of Neonatal Surgery, 2025)
Background: When the median nerve is compressed while passing through the carpal tunnel in the wrist, a condition known as carpal tunnel syndrome (CTS) develops. Purpose: To examine the impact of low intensity pulsed ultrasound on improving biostimulation of median nerve in patients suffering from chronic CTS. Study Design: A pretest posttest control group design. Materials and methods: Fifty-two male and female patients ranging in age from 30 to 50 years old were included in the study with chronic CTS. There were 26 patients in each of the two groups. Those in the 1st group were given through traditional physiotherapy and a low-intensity pulsed ultrasound. The 2nd group of patients served as controls and were given more traditional physiotherapy program, such as the use of splints and rehabilitative exercises. The four weeks of training consisted of three sessions per week. There were pre- and post-treatment assessments of pain levels, distal sensory and motor latencies, pinch grip strengths, and hand functions. Results: In terms of pain intensity, distal sensory and motor latency, pinch grip strength, as well as functional performance, there were significant differences in both groups both before and after treatment. Conclusion: Low intensity pulsed ultrasound was showed to be effective in enhancing perceived wrist pain, sensory and motor distal latency, pinch grip strength and functional performance in patients suffering from chronic CTS.